Analysis of Production Cost Calculation Using Job Order Costing Method at PT Secma Energy Cell - Yeni Elfiza Abbas; Ulil Fadilah (Prodi Akuntansi UIN Sunan Ampel Surabaya, 2024)
Production Cost Calculation is very important for companies as support in financial reporting. Recording production costs encourages business managers to create accurate and fast administrative documentation, so that companies can predict selling price and profit and loss in accordance with expectations. This study aims to examine whether PT Secma Energy Cell, situated in Gresik Regency, East Java, to the principles of cost accounting in implementing the Job Order Costing method for determining production costs. Utilizing a descriptive qualitative approach with a case study methodology, the study aims to evaluate the application of cost calculations for plastic bags and rolls of varying sizes. Data gathering techniques encompass observation, interviews, and documentation of total and variable cost calculations. The study spanned around six months, from December 2022 to May 2023, whereas the data recorded dates back to October 2021. Findings revealed that PT Secma Energy Cell employs a total of 62 individuals, with 34 engaged directly in production activities, while the remainder are non-production staff. Over the course of one month, the company utilized 115,400 kilograms of raw materials, amounting to IDR 2,311,471,500.00, the production of ready-to-sell goods for 1 month was 42,775,005 kg, plastic roll production was 105,020.00 kg, and plastic bag production was 147,795 kg. Up to this point, the company has established the product price per kilogram with an approximately markup of 70%, so that each order received has been calculated in advance regarding the selling price of each product. The analysis revealed that using the Job Order Costing method, the production cost amounted to IDR16,559.48 per kilogram for plastic bags and IDR20,118.81 for plastic rolls. This indicates that PT Secma Energy Cell effectively implements the job order costing method by accurately accounting for expenses associated with raw materials, direct labor, and factory overhead costs. This is intended to enhance the accuracy of the set selling price and potentially boost the company’s future profitability.